FGF21 Attenuated LPS-Induced Depressive-Like Behavior via Inhibiting the Inflammatory Pathway - Wang, Xue; Zhu, Liyun; Hu, Jian; Guo, Ruili; Ye, Shasha; Liu, Fei; Wang, Dongxue; Zhao, Yeli; Hu, Aiping; Wang, Xiaojie; Guo, Kaiming; Lin, Li (Frontiers in Pharmacology, 2020)
Major depressive disorder is a serious neuropsychiatric disorder with high rates of recurrence and mortality. Many studies have supported that inflammatory processes play a central role in the etiology of depression. Fibroblast growth factor 21 (FGF21), a member of the fibroblast growth factors (FGFs) family, regulates a variety of pharmacological activities, including energy metabolism, glucose and lipid metabolism, and insulin sensitivity. In addition, recent studies showed that the administration of FGF21, a regulator of metabolic function, had therapeutic effects on mood stabilizers, indicating that FGF21 could be a common regulator of the mood response. However, few studies have highlighted the antidepressant effects of FGF21 on lipopolysaccharide (LPS)-induced mice, and the anti-inflammatory mechanism of FGF21 in depression has not yet been elucidated. The purpose of the current study was to determine the antidepressant effects of recombinant human FGF21 (rhFGF21). The effects of rhFGF21 on depression-like behaviors and the inflammatory signaling pathway were investigated in both an LPS-induced mouse model and primary microglia in vitro. The current study demonstrated that LPS induced depressive-like behaviors, upregulated proinflammatory cytokines, and activated microglia in the mouse hippocampus and activated the inflammatory response in primary microglia, while pretreatment with rhFGF21 markedly improved depression-like behavior deficits, as shown by an decrease in the total distance traveled and number of standing numbers in the open field test (OFT) and a decrease in the duration of immobility in the tail suspension test (TST) and forced swimming test (FST). Furthermore, rhFGF21 obviously suppressed expression levels of the proinflammatory cytokines interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) and inhibited microglial activation and the nuclear factor-κB (NF-κB) signing pathway. Moreover, coadministration of rhFGF221 with the fibroblast growth factor receptor 1 (FGFR1) inhibitor PD173074 significantly reversed these protective effects, indicating that the antidepressant effects of rhFGF21 occur through FGFR1 activation. Taken together, the results of the current study demonstrated for the first time that exogenous rhFGF21 ameliorated LPS-induced depressive-like behavior by inhibiting microglial expression of proinflammatory cytokines through NF-κB suppression. This new discovery suggests rhFGF21 as a new therapeutic candidate for depression treatment.